2020
DOI: 10.18280/ama_b.631-404
|View full text |Cite
|
Sign up to set email alerts
|

3D Forced Convection in a Box Containing Two Cylindrical Heat Sources

Abstract: Forced convection is a special type of heat transfer in which fluids are forced to move, in order to increase the heat transfer. The aim of this study is to investigate in a numerical simulation of forced convection in a cubic cavity containing two cylindrical heat sources in the middle. The cavity is subjected to an inflow of air inlet from the left and an outlet flow from the right side with the same dimensions of the opening doors (0.1 H). The walls of the cavity are maintained adiabatic. The conservation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Time marching is handled by the fully implicit scheme. For the convective terms, second order upwind scheme is employed and the algorithm applied for coupling the velocity and pressure fields is SIMPLER (Rahman et al 2009;Bouabdallah et al 2020 ). The convergence is attained when the residuals are less than 10 -4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time marching is handled by the fully implicit scheme. For the convective terms, second order upwind scheme is employed and the algorithm applied for coupling the velocity and pressure fields is SIMPLER (Rahman et al 2009;Bouabdallah et al 2020 ). The convergence is attained when the residuals are less than 10 -4 .…”
Section: Methodsmentioning
confidence: 99%
“…Alshomrani et al (2019) also considered 3D free convection in a cubical cavity with different positions of heater and cooler, and they indicated the significant role of cooler location, Ra number and aspect ratio in the energy transport convective cooling flow inside the enclosure. Recently, Bouabdallah et al (2020) studied numerically the 3D forced convection in a cubic cavity containing two cylindrical heat sources in the middle and Chati et al (2021b) numerically analyzed the turbulent mixed convective heat transfer in a ventilated enclosure with a cylindrical/cubical heat source. They showed that the ventilation efficiency of the cavity including the cylindrical heat source is better.…”
Section: Introductionmentioning
confidence: 99%
“…h = 5 W/m² .K and T0 = 300 K). To simulate the airflow under the greenhouse, we have used the software Ansys-Fluent, which solves the Navier-Stokes equations ( [16,17]) using finite volume method. It is proposed to assimilate the plant cover to a porous medium.…”
Section: Figure 1 Geometry Of the Modelmentioning
confidence: 99%
“…Besides, pure mixed convection for a heated rotating cylinder inside such a cavity was examined by Priam et al [13]. Bouabdallah et al [14] and Kherroubi et al [15] studied similar heat transfer studies for forced and mixed convection utilizing such cavity-shaped geometry and various heated surface conditions. Nosonov et al [16] numerically studied the conjugate mixed convection phenomenon in a rectangular cavity with local heaters.…”
Section: Introductionmentioning
confidence: 99%
“…Bouabdallah et al. [14] and Kherroubi et al. [15] studied similar heat transfer studies for forced and mixed convection utilizing such cavity‐shaped geometry and various heated surface conditions.…”
Section: Introductionmentioning
confidence: 99%